Genderové role v rodině pohledem dětských aktérů - Lenka Slepičková; Michaela Bartošová Kvapilová (Gender a Výzkum)
The article is based on research conducted with young children, and uses methods of data collection that are suitable and appropriate for children (focus groups, writing, and drawing). Theoretically grounded in a child-perspective research, we intend to contribute to the debate on the transition of gender order in the Czech environment. The text focuses particularly on the issue of gender roles both in the family of participating children and in their projections of roles of individual family members. An analysis of children’ views shows that they identify with the gender categories of “men” and “women” and construct these categories as opposite and firmly bounded. Despite the awareness of conflicts and problems that the unequal distribution of domestic tasks can bring, children mostly support the traditional division of roles and refer to them as normal, natural and corresponding to the physical characteristics of men and women. On the other hand, egalitarian attitudes (the view of division of roles as not depending on gender) are expressed by some children, more often by children from the urban school than from the village school.